2021
DOI: 10.1016/j.eclinm.2021.101116
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying the risk of NAFLD in patients with HIV under combination antiretroviral therapy (cART)

Abstract: Background De novo steatosis is the main criteria for non-alcoholic fatty liver disease (NAFLD), which is becoming a clinically relevant comorbidity in HIV-infected patients. This may be due to the HIV virus itself, as well as long-term toxicities deriving from antiretroviral therapy. Therefore, HIV infected patients require prevention and monitoring regarding NAFLD. Methods This study investigated the differential role of body mass index (BMI) and combination antiretro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 40 publications
3
60
2
Order By: Relevance
“…Strikingly, a higher risk of increased liver fibrosis was associated to longer cumulative TAF exposure according to APRI and FIB-4 scores and to a longer cumulative RAL exposure among those with liver stiffness ≥F2 at TE. These data are in line with previously published data, which showed that both drugs were associated with a significant weight gain after initiation of therapy and with development and progression of liver steatosis [ 62 ]. The accumulation of fat can cause liver inflammation, hepatic cell death and steatohepatitis, leading to faster progression of liver fibrosis over time in the absence of an effective intervention for harm reduction.…”
Section: Discussionsupporting
confidence: 93%
“…Strikingly, a higher risk of increased liver fibrosis was associated to longer cumulative TAF exposure according to APRI and FIB-4 scores and to a longer cumulative RAL exposure among those with liver stiffness ≥F2 at TE. These data are in line with previously published data, which showed that both drugs were associated with a significant weight gain after initiation of therapy and with development and progression of liver steatosis [ 62 ]. The accumulation of fat can cause liver inflammation, hepatic cell death and steatohepatitis, leading to faster progression of liver fibrosis over time in the absence of an effective intervention for harm reduction.…”
Section: Discussionsupporting
confidence: 93%
“…However, the prevalence of significant liver fibrosis in PWH without NAFLD was still 9.2%, pointing out that HIV mono-infected patients can develop significant liver fibrosis in the absence of NAFLD. These liver fibrosis cases may be due to risk factors for liver disease other than the metabolic ones and that are unique to HIV infection, including chronic inflammation and exposure to ART [20,51]. Indeed, patients with significant liver fibrosis and without NAFLD had a lower CD4 cell count and a higher proportion of exposure to didanosine, while metabolic comorbidities and high BMI were less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the most studied and the most aggressive type of cellular toxicity is represented by the mitochondrial toxicity (197) induced by NRTIs, NNRTIs, PIs and by some INSTI representatives (198,199). This may occur shortly after ART starting and may be perpetuated depending on various risk factors (197,(199)(200)(201).…”
Section: Hiv Metabolic Alterationsmentioning
confidence: 99%
“…Both mitochondrial dysfunction and the metabolic changes play a decisive role in the development of HALS ( 194 , 202 ) and favor liver steatosis and NAFLD development ( 194 ) as can be seen in the Figure 2 . The degree of liver toxicity becomes apparent after 6-8 months of NRTI treatment ( 203 ) and differs depending on the type of NRTI and its persistence within the cell ( 200 , 201 ). MetS also develops as a consequence of ART-mitochondrial toxicity ( 202 , 204 ) and of visceral adipose tissue imbalance induced by hepatokines/adipokines disequilibrium ( 205 ).…”
Section: Hiv and Hbv Role In Nafld Pathogenesis And In The Breakdown ...mentioning
confidence: 99%